1989
DOI: 10.1007/bf01739967
|View full text |Cite
|
Sign up to set email alerts
|

Pressure sensitivity of active tension in glycerinated rabbit psoas muscle fibres: Effects of ADP and phosphate

Abstract: The effect of changes in hydrostatic pressure (up to 10 MPa) on the maximally calcium-activated tension in glycerinated rabbit psoas fibres has been examined. The steady active tension was depressed by 0.8% per MPa pressure rise. This pressure sensitivity was enhanced by the pressure of millimolar phosphate and depressed by millimolar ADP. These results support the conclusions that increased pressure is perturbing a crossbridge event. The results are discussed in terms of a three state crossbridge model and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
32
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 22 publications
4
32
0
Order By: Relevance
“…The steady tension in a fused tetanic contraction was typically reduced at increased hydrostatic pressure and it was comparable to the pressure-induced tension depression obtained in maximally Ca2"-activated skinned muscle fibres; this was attributed to an effect of high pressure on cycling cross-bridges (Geeves & Ranatunga, 1987;Fortune, Geeves & Ranatunga, 1989. Additionally, we argued that a small reduction in active tension in muscle fibres was expected from studies on the interaction between isolated actin and myosin subfragment-i (SI) in solution (Coates, Criddle & Geeves, 1985), which showed that high pressure inhibits a particular isomerization between two acto-Si complexes.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…The steady tension in a fused tetanic contraction was typically reduced at increased hydrostatic pressure and it was comparable to the pressure-induced tension depression obtained in maximally Ca2"-activated skinned muscle fibres; this was attributed to an effect of high pressure on cycling cross-bridges (Geeves & Ranatunga, 1987;Fortune, Geeves & Ranatunga, 1989. Additionally, we argued that a small reduction in active tension in muscle fibres was expected from studies on the interaction between isolated actin and myosin subfragment-i (SI) in solution (Coates, Criddle & Geeves, 1985), which showed that high pressure inhibits a particular isomerization between two acto-Si complexes.…”
supporting
confidence: 52%
“…The basic design features of the pressure chamber were published by Geeves & Ranatunga (1987), the design of the transducer assembly by Fortune et al (1989) and the methodology used in recording transient tension responses following rapid (<1Ims) pressure release is described by Fortune et al (1991). MS 2132, pp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In both fibre types, the addition of 10 mÒ BDM inhibited active contractions and abolished stretch activation seen at high temperatures (see Mutungi & Ranatunga, 1996a), but had no effect on the stretch-induced passive tension response. Experiments were also done to examine the main effects of chemical skinning on the passive tension components in fast and slow fibres: the relaxing solutions used for these experiments were similar to those described by Fortune, Geeves & Ranatunga (1989) and Ranatunga (1994) and they contained 5-10 mÒ MgATP and 15-20 mÒ EGTA (pH 7-7·1; ionic strength, 180-200 mÒ). The experiments were done at 10°C and a full set of data at a range of stretch velocities was initially collected from a preparation before skinning.…”
Section: Methodsmentioning
confidence: 99%
“…The experiments were done at 10°C and a full set of data at a range of stretch velocities was initially collected from a preparation before skinning. Then the Ringer solution was quickly replaced with skinning solution containing 0·5% Brij (Brij 58, Aldrich;Fortune et al 1989) while the preparation was still connected to the recording assembly. A preparation remained exposed to skinning solution for 1 h before a second set of passive tension responses was recorded in standard relaxing solution, for comparison with the responses from the intact preparation.…”
Section: Methodsmentioning
confidence: 99%